2012
DOI: 10.15809/irriga.2012v1n01p309
|View full text |Cite
|
Sign up to set email alerts
|

Solução Alternativa Para Bombeamento De Água E Automação Da Irrigação Sem O Uso De Energia Elétrica

Abstract: RESUMOO uso econômico da água garantirá que políticas e práticas de irrigação sejam sustentáveis, para que no futuro um terço da alimentação mundial possa continuar a vir de 15% da superfície terrestre do planeta. Em algumas regiões do Brasil, existem inúmeras propriedades rurais que não possuem o fornecimento público de energia elétrica. Nesses locais, para que a agricultura irrigada moderna e automatizada possa ser introduzida é necessária a utilização de bombas e equipamentos que dispensam o emprego de ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
1
Order By: Relevance
“…Despite the modernization of agriculture in recent years, many farms, mostly small and medium-sized ones, still employ manual irrigation because automated systems typically involve high installation and maintenance costs, making it difficult for small and medium-sized producers to use them. Grah et al (2012) conducted an assessment of irrigation systems and concluded that automated systems were better than conventional methods because they save water and increase crop yields. The authors were also concerned with the lack of electricity in some regions and thus developed an autonomous irrigation system that uses hydraulic-mechanical power as an alternative irrigation pumping system for places lacking electricity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the modernization of agriculture in recent years, many farms, mostly small and medium-sized ones, still employ manual irrigation because automated systems typically involve high installation and maintenance costs, making it difficult for small and medium-sized producers to use them. Grah et al (2012) conducted an assessment of irrigation systems and concluded that automated systems were better than conventional methods because they save water and increase crop yields. The authors were also concerned with the lack of electricity in some regions and thus developed an autonomous irrigation system that uses hydraulic-mechanical power as an alternative irrigation pumping system for places lacking electricity.…”
Section: Introductionmentioning
confidence: 99%
“…Losses of water through evaporation or drift is minimized, as well as fungicidal diseases. The volume of water for localized irrigation is smaller when compared to other application methods, being an advantage for places where water resources are scarce or that face conflicts over water use (Grah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, na irrigação localizada o volume de água utilizado é menor quando comparado aos demais métodos de irrigação, sendo vantajosa sua aplicação em locais onde há limitação ou escassez de recursos hídricos ou ainda que enfrentem conflitos pelo uso da água. (GRAH et al, 2012) Um dos principais fatores de produção na agricultura é a água, sendo que cada espécie de planta necessita de um adequado nível de água no solo para atender suas necessidades fisiológicas (MANTOVANI et al, 2012).…”
Section: Introductionunclassified